Faecalibacterium longum alleviates high-fat diet-induced obesity and protects the intestinal epithelial barrier in mice - Haoyu Wang; Shengnan Yu; Kunyi Zhao; Tongyuan Hu; Zhinan Wu; Hewei Liang; Xiaoqian Lin; Luwen Cui; Jingtong Yao; Xiaomin Liu; Xin Tong; Ningning He; et al. (Gut Microbes Reports)
Numerous studies have indicated that depletion of Faecalibacterium is related to obesity. Here we show that Faecalibacterium longum CM04–06 out of 29 strains of the Faecalibacterium genus annotated in CGR2 exhibited the strongest inverse correlation with body mass index (BMI) in a cohort of 1120 han Chinese individuals. Administration of F. longum CM04–06 to mice prevented high-fat diet (HFD)-induced obesity, improved glucose tolerance, reduced adipose tissues mass, and liver steatosis. Supplementation with F. longum CM04–06 reduced the level of pro-inflammatory cytokines in liver, colon, and circulation. F. longum CM04–06 protected the intestinal epithelial barrier increasing the expression of tight junction proteins. Metagenomic sequencing indicated that F. longum supplementation did not change the overall composition of the gut microbiota in mice, but selectively increased the relative abundance of Staphylococcus xylosus and Staphylococcus nepalensis. In conclusion, our results point to a potential therapeutic potential of F. longum CM04–06.